Reliability and validity of an FFQ for South American children and adolescents from the SAYCARE study (2019)
ABSTRACT: Objective: The purpose of this study was to analyse the reliability and validity of a semi-quantitative FFQ to assess food group consumption in South American children and adolescents. Design: The SAYCARE (South American Youth/Child cARdiovascular and Environmental) study is an observational, multicentre, feasibility study performed in a sample of 3- to 18-year-old children and adolescents attending private and public schools from six South American countries. Participants answered the FFQ twice with a two-week interval and three 24-h dietary recalls. Intraclass and Spearman’s correlations, weighted Cohen’s kappa (κw), percentage of agreement and energy-adjusted Pearson’s correlation coefficients were calculated. Setting: Seven cities in South America (Buenos Aires, Lima, Medelin, Montevideo, Santiago, Sao Paulo and Teresina). Subjects: A sample of 200 children and 244 adolescents for reliability analyses and 252 children and 244 adolescents for validity analyses were included. Results: Depending on the food group, for children and adolescents, reliability analyses resulted in Spearman’s coefficients from 0·47 to 0·73, intraclass correlation coefficients from 0·66 to 0·99, κw coefficients from 0·35 to 0·63, and percentage of agreement between 72·75 and 83·52 %. In the same way, validity analyses resulted in Spearman’s coefficients from 0·17 to 0·37, energy-adjusted Pearson’s coefficients from 0·17 to 0·61, κw coefficients from 0·09 to 0·24, and percentages of agreement between 45·79 and 67·06 %. Conclusion: The SAYCARE FFQ achieved reasonable reliability and slight-moderate validity for almost all food groups intakes. Accordingly, it can be used for the purpose of ranking the intake of individuals within a population.